Radiation Oncology for Pediatric CNS Tumors (Springer International Publishing, 2018)
This book reviews the principles and applications of radiotherapy in the management of pediatric brain tumors to allow the reader to gain a full appreciation of the major aspects involved in caring for these patients. Individual sections are devoted to basic principles, specific management for the full range of tumor entities, radiotherapy techniques, and potential toxicities and their management. The book is written and edited by world leaders in pediatric radiotherapy, and care has been taken to cover the latest advances in diagnosis and radiotherapy techniques. Pediatric brain tumors represent a diverse group of neoplasms that require carefully planned management for successful definitive treatment. Radiotherapy is one of the fundamental components in treatment for the majority of these vulnerable patients. The optimal radiation therapy approach will depend on multiple factors, including tumor type and location, extent of disease, age of the patient, and other therapies. A thorough understanding of the natural history of the disease, communication with the multidisciplinary team, full knowledge of available radiotherapy techniques, and consideration of potential acute and late toxicities are therefore essential for each patient. .